2011
DOI: 10.1016/j.bej.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring lentiviral vector production kinetics using online permittivity measurements

Abstract: Lentiviral vectors (LVs) are effective delivery vehicles that have been successfully used in gene and cell therapy. LVs are most commonly produced via the transient transfection of several plasmid constructs in adherent cell cultures. Recently, we described an efficient and scalable LV production in serum-free suspension cultures. To further facilitate the translation of LV-based interventions to the clinic, the robustness of the production process needs to be ensured to ultimately achieve a specified quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 67 publications
2
20
0
Order By: Relevance
“…However, all of the events occurring in a cell system during viral infection (virion entrance, viral protein synthesis, bud formation, and progeny viral release) could potentially affect the cell's dielectric properties and be detected at a macroscopic level. This was recently documented by our group with lentiviral productions using HEK293 suspension cell cultures 38…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…However, all of the events occurring in a cell system during viral infection (virion entrance, viral protein synthesis, bud formation, and progeny viral release) could potentially affect the cell's dielectric properties and be detected at a macroscopic level. This was recently documented by our group with lentiviral productions using HEK293 suspension cell cultures 38…”
Section: Introductionmentioning
confidence: 63%
“…From the results established at small‐scale and considering the potential of the multifrequency permittivity scan to monitor viral productions,33, 37, 38 influenza kinetics have been extensively documented to detect infection‐cycle events using an on‐line signal. Both virion formation and cell death, including apoptosis and necrosis, are major cellular events that impact the membrane capacitance ( C M ) and intracellular conductivity (σ i ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, perfusion is not only used for production at high cell density but also for continuous harvest of viral product. Ansorge et al reported sustained lentivirus perfusion production with viral titers between 10 7 and 10 8 IVP/ml using feeding rates of 1-2 vol/day [82]. Several authors showed the use of perfusion for retrovirus production (reviewed in [83]).…”
Section: Continuous Feedingmentioning
confidence: 97%
“…It has been implemented in batch and fed-batch cultures, as well as in packed bed reactors. This method has also been dedicated to monitor production levels of viruses (lentivirus, baculovirus) or proteins, but also evolution of cell size or of processes (Zeiser et al 2000;Ansorge et al 2010Ansorge et al , 2011Cannizzaro et al 2003). A single group applied this method to adherent CHO cells cultivated on macroporous microcarriers (Ducommun et al 2001(Ducommun et al , 2002.…”
Section: Introductionmentioning
confidence: 99%